EVALUATION OF THE ASSESSMENT INFORMATION SYSTEM PROGRAM (ISP) BANDUNG JUARA IN THE GOVERNANCE SECTION OF THE REGIONAL SECRETARIAT OF THE CITY OF BANDUNG - Nyi Raden Ruyani; Andre Ariesmansyah; Elika Dewi Faustine (International Journal of Social Science, 2022)
Every government either central or regional is often required to always innovate, especially in the activities of qualified public servants. One of them is innovation whose activities are spread across each region in the city of Bandung is the Bandung Champion Assessment Information System (SIP), which is a program built to assess the performance results of each camat and lurah in public service, the implementation of evaluation is measured based on the results of the activity report uploaded to the SIP Bandung Champion website, camat and lurah evaluation activities have several stages to get the final results of the assessment. The purpose of this research is to analyze and describe the Evaluation of The Bandung Champion Assessment Information System (SIP) Program in the Governance Section of the Bandung City Regional Secretariat to know. The research method used is qualitative with a descriptive approach. Data collection techniques are used with literature studies, observations, documents and interviews. To measure the evaluation of SIP program Bandung Champion researchers use the Program Evaluation Theory which has indicators Of Evaluation Context, Evaluation Input, Evaluation Process, Product Evaluation (CIPP). This research, that the evaluation of the Bandung Champion SIP Program has problems in performance has not been maximal, citizen assessment activities are not realized.